PELATIHAN DAN LINGKUNGAN KERJA PENGARUHNYA TERHADAP KEPUASAN KERJA PEGAWAI PUSKESMAS KOTA BARU KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR - jurnalmap map (MAP (Jurnal Manajemen dan Administrasi Publik), 2022)
The purpose of this study is to describe the training and work environment its effect on job satisfaction in the Kota Baru Health Center, Keritang District, Indragiri Hilir District. This research approach is a quantitative study using a questionnaire as a tool to collect data. The number of samples were 60 respondents, all employees of the Kota Baru Public Health Center, Keritang Subdistrict, Indragiri Hilir Regency were made respondents in the study. Results showed that the training had a partial effect on job satisfaction. The work environment has a partial effect on job satisfaction. The F test results of training and work environment simultaneously have a positive and significant effect on job satisfaction. The results of the coefficient of determination test indicate that the effect of training and work environment on job satisfaction by 71%, while the remaining 29% can be explained by other variables outside of the research variables.